Internet of things-based electrical energy control and monitoring in households using spreadsheet datalogger - Jannah, Misbahul; Hasibuan, Arnawan; Kartika, Kartika; Asran, Asran; Yunizar, Zara; Usrina, Nura; Nuryawan, Nuryawan; Almunadiansyah, Rizky (Institute of Advanced Engineering and Science, 2024)
Today, the demand for electrical energy is paramount in various daily activities. Hence, individuals must be aware of the amount of electrical energy consumed to maintain the quality of electronic devices. Knowing the quality of electronic devices is essential since it can impact the performance and lifespan of electrical equipment. The value of electrical power is determined by the quality of electrical power and the number of hours. Monitoring electrical energy involves collecting or measuring data to assess the current level of energy consumption. The author is interested in researching the use of Datalogger Spreadsheets to monitor and gather real-time information on energy use, which is made possible through integration with internet of things (IoT) and microcontrollers. Through data analysis and observation, solutions to existing problems are sought by comparing and matching data. Monitoring daily energy usage in a home setting produces output data that can be viewed directly and remotely with real-time results. This tool is expected to address current issues.